Efficacy and safety of photodynamic therapy for non–muscle-invasive bladder cancer: a systematic review and meta-analysis - Li, Haitao; Long, Gongwei; Tian, Jun (Frontiers in Oncology, 2023)
Background: Photodynamic therapy (PDT) is a promising treatment for non-muscle-invasive bladder cancer (NMIBC), we conducted this systematic review to comprehensively assess its efficacy and safety. Methods: A comprehensive literature research was conducted using PubMed, Web of Science, and Scopus, and studies reporting the safety and efficacy of PDT in NMIBC were included. Complete response (CR) rates, recurrence-free survival (RFS) at different time points, and complication incidences were extracted and synthesized. Pooled results were presented as rates with a 95% confidence interval (95% CI). Results: Overall, 28 single arm studies were included in the meta-analysis. For unresectable NMIBC, therapeutic PDT achieved CR in 68% (95% CI: 59%-77%) of patients. Among these CR cases, 71% (95% CI: 56%-85%) and 38% (95% CI: 12%-64%) have a RFS longer than 12 and 24 months, respectively. For Tis patients, the CR rate was 68% (95% CI: 56%-80%), and 84% (95% CI: 48%-100%) and 13% (95% CI: 1%-32%) have a RFS longer than 12 and 24 months. For patients with resectable tumors, post-resection adjuvant PDT could provide a 12 and 24 months RFS in 81% (95% CI:76%-87%) and 56% (95% CI:41%-71%) of them. Especially, for NMIBC patients who failed BCG therapy, adjuvant PDT could still achieve a 1-year and 2-year RFS in 68% (95% CI:51%-86%) and 56% (95% CI:32%-81%) patients. The complications were mostly mild and transient, including lower urinary tract symptoms and photosensitivity. Conclusion: Both therapeutic and adjuvant PDT present satisfying safety and efficacy for NMIBC, including these cases that are resistant to the standard of care. As a promising option for NMIBC, PDT deserves further exploration by future high-quality research.